The Role of Community Empowerment on Sustainable Tourism Development and Creative Economy and Its Impact on Community Wellbeing in Bandung - Hutajulu, Huta Parlinggoman; Indrajaya, Danang (International Journal of Economics Development Research (IJEDR), 2025)
The decrease in the number of foreign tourists and tourism foreign exchange receipts due to the COVID-19 pandemic shows how vulnerable Indonesia's tourism sector is to global crises. Before the pandemic, tourist visits and foreign exchange earnings demonstrated a significant upward trend, but the imposition of travel restrictions and the closure of tourist destinations caused a drastic decline, directly affecting the tourism industry and the creative economy. This condition emphasizes the urgent need for a sustainability-based tourism model that is less dependent on foreign tourists and more resilient to external shocks. This study aims to analyze the influence of community empowerment on sustainable tourism development and the creative economy in Bandung, as well as how these three variables collectively influence community wellbeing. A descriptive-quantitative approach was employed, with data collected from 385 respondents involved in the tourism and creative sectors. The data were analyzed using the Partial Least Squares (PLS) method, which allows simultaneous testing of complex relationships between latent variables. The results indicate that community empowerment has a significant influence on both sustainable tourism development and the creative economy. Furthermore, both sustainable tourism development and the creative economy significantly influence community wellbeing. The study also finds that sustainable tourism development mediates the effect of community empowerment on community wellbeing, as does the creative economy. These findings confirm the importance of strengthening community empowerment policies through skill development, improved access to markets, and enhanced collaboration between the government, local communities, and the private sector. Such measures are crucial to building inclusive and sustainable economic opportunities in the tourism and creative economy sectors, particularly in urban regions like Bandung that rely on local innovation and community participation for long-term resilience and growth.